Certainty of Response Index-based E-Diagnostics Assisted by Google Forms to Identify Misconceptions in Simple Harmonic Waves - Pribadi, Farchan Oktavianto; Supahar; Afriwardani, Pinandita (Journal of Education Reseach and Evaluation, 2023)
Physics learning plays a very important role in everyday life, therefore, students' understanding of physics material is very important. Students who understand physics concepts well will find it easier to apply these physics concepts in everyday life. However, some students had difficulty understanding physics material, especially when they misunderstood the concept. Physics concepts formed webs that were connected to one another, so that a correct understanding at the previous level was one of the determining factors for success. The purpose of this research was to develop an e-Diagnostic based on the Certainty of Response Index (CRI) with the help of Google Forms to identify students' misconceptions about simple harmonic motion material. The type of research used was Research and Development which was adapted from the Four-D model. Grade 10 students were used as research subjects. The data described were in the form of instrument validity and results of identifying misconception profiles in students. The results of the validity test conducted by 2 experts and 8 colleagues stated that the developed test instrument was feasible to use. The results of the identification of misconceptions that were carried out showed that there were misconceptions, especially in the restoration style sub-topic. In conclusion, the e-Diagnostics that was developed is feasible to use as a tool to identify student misconceptions.